Accounting For Islamic Housewives On Savings For Basic Necessities For Eid Al-Fitr - Diantoro, Femba Akris (INAIFAS Press, 2024)
This article aims to discuss accounting for Islamic housewives regarding saving for basic needs ahead of Eid al-Fitr, which is a special day for Muslims all over the world, where before the holiday usually the price of basic necessities will increase significantly, therefore Islamic housewives must prepare special recording in the form of savings or wadi’ah by managing family income funds. A descriptive qualitative research method that brings the phenomenon closer to housewives' finances in preparation for Eid. The results of this research are that it is not just the costs shown in household records or transparency, but the practice of a housewife's responsibility which must be competent, accountable in managing family funds in a simple form showing an attitude of discipline that brings about family harmony and an Islamic outlook on life. a belief can be held accountable before God in the future.